2012
DOI: 10.2340/00015555-1286
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Distribution of Hyaluronan in Psoriatic Arthritis; Coexistence of CD44, MMP3 and 9

Abstract: Psoriatic arthritis is a chronic systemic disease in which patients develop persistent inflammation of the skin and joints, leading to disability and joint damage. The extracellular component hyaluronan (HA) plays an important role in regulatory processes such as inflammation, wound healing and tumour progression. At any site of inflammation HA can be depolymerized to low-molecular weight fragments, which, in turn, induce an array of inflammatory mediators that can lead to chronic inflammation. This study desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…We have previously reported the interest of measuring levamisole and cocaine in hair samples in a patient presenting an atypical panniculitis with some features of vasculitis and positive ANCA testing. 3 Herein, we report additional data that reinforce the link between levamisole exposure and development of systemic vasculitis. In May 2011, a 39-year-old female cocaine addict (previously reported 3 ) consulted for recurrent (six stereotypic episodes per year) painful panniculitis with erythematous…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…We have previously reported the interest of measuring levamisole and cocaine in hair samples in a patient presenting an atypical panniculitis with some features of vasculitis and positive ANCA testing. 3 Herein, we report additional data that reinforce the link between levamisole exposure and development of systemic vasculitis. In May 2011, a 39-year-old female cocaine addict (previously reported 3 ) consulted for recurrent (six stereotypic episodes per year) painful panniculitis with erythematous…”
mentioning
confidence: 66%
“…Additionally, recent studies have also suggested that serum hyaluronic acid did not correlate with joint inflammation in psoriatic arthritis. 3 Recent progress has demonstrated that hyaluronan is an important immune regulator in various diseases. In particular, low molecular weight hyaluronan is a ligand for toll-like receptors (TLRs), and induces inflammatory cytokine gene expression.…”
mentioning
confidence: 99%
“…However, some earlier studies have failed to show the inflammatory properties of LMHA (12,13). In our earlier study of PsA, inflammation in skin of differing classification groups revealed a redistribution of HA in involved and non-involved psoriatic skin with epidermal imbalance between HA and its receptor CD44 in untreated patients with polyarticular disease (4).…”
mentioning
confidence: 79%
“…Patients with PsA usually exhibit low-grade skin inflammation (3). However, in a previous study, we showed that patients with PsA can exhibit inflammatory changes in both lesional and non-lesional skin (4). Moreover, in psoriatic patients with neither joint complaints nor disease, about half have shown entheseal inflammation at the Achilles tendon insertion.…”
mentioning
confidence: 81%
“…In Laugier's study , immunohistochemistry of the skin showed that HA was expressed only in the basal cells and basal upper layers of the epidermis and not inside the granular layer and stratum corneum. http://www.ncbi.nlm.nih.gov/pubmed/?term=Lindqvist%20U%5BAuthor%5D&cauthor=true&cauthor_uid=22278305 found that HA was mainly distributed within the papillary layer's intercellular regions of normal skin, which exhibited strong and non‐uniform staining distribution inside the reticular layer of dermis. In addition, the epidermal basement membrane area was the region that had the most intense staining.…”
Section: Discussionmentioning
confidence: 99%